Theory of mind impairment in Huntington's disease patients and their relatives - Leo Bayliss; Víctor Galvez; Adriana Ochoa-Morales; Mireya Chávez-Oliveros; Yaneth Rodríguez-Agudelo; Guillermo Delgado-García; Marie Catherine Boll (Arquivos de Neuro-Psiquiatria)
ABSTRACT Huntington disease (HD) is an autosomal dominant genetic disorder characterized by movement disorders, cognitive impairment, and psychiatric symptoms. Relatives of HD patients experience a great burden as the latter suffer from altered social conduct and deterioration of interpersonal relationships. Theory of mind (ToM) is the ability to attribute mental states (to oneself and others). Deficits in ToM are thought to have a role in the changes in empathy and interpersonal difficulties that HD patients face. Methods: We conducted a cross sectional study to compare ToM task scores of patients with mild to moderate HD, their relatives (spouse or at-risk first-degree relative with a negative gene test) and controls.Individuals with dementia or depression were excluded. The ToM test battery included Spanish versions of the Reading Mind in the Eyes Test (RMET), Happé's Strange Stories (Social and Physical Stories subtests) and the Hinting Task. Results: The series comprised 12 HD patients, 12 relatives and 12 controls. The HD patients showed lower affective ToM scores than controls (RMET 19 [3.5] vs 23.9 [2.7], p = 0.016). Cognitive ToM tasks scores were lower in HD patients than controls as well (Happé's Social Stories 9 [2.6] vs 13 [1.9], p = 0.001; the Hinting Task 13.6 [3.4] vs 17.5 [4.0], p = 0.009). In the Hinting Task, HD relatives had lower scores in than controls (13 [3.2] vs 17.5 [4.0], p = 0.009) and similar scores to controls in the rest of the battery. Conclusion: The HD patients with mild to moderate disease severity and their relatives show ToM deficits.